(untitled) (International journal of artificial intelligence, 2026)
This study examines the main translatological challenges encountered in translating the interview genre between English and Uzbek. The research analyzes the genre-specific features of interviews, their dialogic structure, question–answer dynamics, and the influence of pragmatic factors on translation. It also investigates how structural, semantic, and stylistic differences between the two languages affect equivalence and adequacy. Based on authentic interview materials, key translation difficulties are identified, and effective strategies for overcoming them are proposed. The findings hold both theoretical and practical significance for English–Uzbek translation studies.